Mummy Portraits of Roman Egypt - Cartwright, Caroline (Getty Publications, 2020)
This publication presents fascinating new findings on ancient Romano-Egyptian funerary portraits preserved in international collections. Once interred with mummified remains, nearly a thousand funerary portraits from Roman Egypt survive today in museums around the world, bringing viewers face-to-face with people who lived two thousand years ago. Until recently, few of these paintings had undergone in-depth study to determine by whom they were made and how.